Etika Berbangsa Dan Bernegara Dalam Islam - Usman Sutisna (Al Ashriyyah, 2019)
This article aims to be a guideline for the general public about how we behave and uphold Islamic religious values regarding the ethics of the nation and state. This is felt to be quite important by paying attention to the phenomena and the many cases related to the fading of understanding as well as awareness as citizens who must have ethics in doing all actions that are responsible for the good and progress of the nation. Modernization and the rapid flow of globalization contribute to the weakening of public awareness in upholding the values and norms that must be a reference in behavior, so these conditions must require special attention for us all in order to maintain the integrity and national unity, especially our nation is a nation that is very diverse in all lines, both religion, race, ethnicity, culture and between groups.